National framework for ranking lakes by potential for anthropogenic hydro-alteration. (March 2021) - Fergus, C. Emi; Brooks, J. Renée; Kaufmann, Philip R.; Pollard, Amina I.; Herlihy, Alan T.; Paulsen, Steven G.; Weber, Marc H.
Highlights: US lakes ranked on gradient of hydro-alteration potential using dam & land use data. 50% of US lakes have dams & land use with great potential to alter lake hydrology. HydrAP rank associations with lake water-level change varied by ecoregion. West and Appalachians lakes with high HydrAP ranks had large water-level change. HydrAP provides tool to evaluate anthropogenic drivers of lake hydro-alteration. Lakes with no potential for human hydro-alteration decreased from 2007 to 2012. Abstract: Lakes face multiple anthropogenic pressures that can substantially alter their hydrology. Dams and land use in the watershed (e.g., irrigated agriculture) can modify lake water regimes beyond natural ranges, and changing climate may exacerbate anthropogenic stresses on lake hydrology. However, we lack cost-effective indicators to quantify anthropogenic hydrologic alteration potential in lakes at regional and national extents. We developed a framework to rank lakes by the potential for dams and land use to alter lake hydrology (HydrAP) that can be applied at a national scale. The HydrAP framework principles are that 1) dams are primary drivers of lake hydro-alteration, 2) land use activities are secondary drivers that alter watershed hydrology, and 3) topographic relief limits where land use and dams are located on the landscape. We ranked lakes in the United States Environmental Protection Agency National Lakes Assessment (NLA) on a HydrAP scale from zero to seven, where a zero indicates lakes with no potential for anthropogenic hydro-alteration, and a seven indicates large dams and/or intensive land use with high potential to alter lake hydrology. We inferred HydrAP population distributions in the conterminous US (CONUS) using the NLA probabilistic weights. Half of CONUS lakes had moderate to high hydro-alteration potential (HydrAP ranks 3–7), the other half had minimal to no hydro-alteration potential (HydrAP ranks 0–2). HydrAP ranks generally corresponded with natural and man-made lake classes, but >15% of natural lakes had moderate to high HydrAP ranks and 10% of man-made lakes had low HydrAP ranks. The Great Plains, Appalachians, and Coastal Plains had the largest percentages (>50%) of high HydrAP lakes, and the West and Midwest had the lowest percentages ( 30%). Water residence time (τ) and water-level change were associated with HydrAP ranks, demonstrating the framework's intended ability to differentiate anthropogenic stressors that can alter lake hydrology. High HydrAP lakes had shorter τ in all ecoregions, but HydrAP relationships with water-level change varied by ecoregion. In the West and Appalachians, high HydrAP lakes experienced excessive water-level declines compared to low-ranked lakes. In contrast, high HydrAP lakes in the Great Plains and Midwest showed stable water levels compared to low-ranked lakes. These differences imply that water management in western and eastern mountainous regions may result in large water-level fluctuations, but water management in central CONUS may promote water-level stabilization. The HydrAP framework, using accessible national datasets can support large-scale lake assessments and be adapted to specific locations where data are available.